2001
DOI: 10.1093/geront/41.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of a Home Environmental Intervention

Abstract: The environmental program appears to have a modest effect on dementia patients' IADL dependence. Also, among certain subgroups of caregivers the program improves self-efficacy and reduces upset in specific areas of caregiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
110
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(117 citation statements)
references
References 33 publications
2
110
0
5
Order By: Relevance
“…RCTs have been used for interventions that have introduced specialized designs into the home (e.g., Gitlin et al 2001Gitlin et al , 2006; but when the physical environment is the intervention, most public contexts make it diffi cult to use RCTs and other experimental intervention designs (e.g., randomized/non-randomized, controlled/uncontrolled, pre-/post-). The many practical barriers include the high costs and relative permanence of many physical environmental interventions; the costs, time, and diffi culty of changing intervention, particularly in crossover designs; and the disruption caused by installing or constructing environmental interventions.…”
Section: Lack Of Appropriate Experimental Designsmentioning
confidence: 99%
“…RCTs have been used for interventions that have introduced specialized designs into the home (e.g., Gitlin et al 2001Gitlin et al , 2006; but when the physical environment is the intervention, most public contexts make it diffi cult to use RCTs and other experimental intervention designs (e.g., randomized/non-randomized, controlled/uncontrolled, pre-/post-). The many practical barriers include the high costs and relative permanence of many physical environmental interventions; the costs, time, and diffi culty of changing intervention, particularly in crossover designs; and the disruption caused by installing or constructing environmental interventions.…”
Section: Lack Of Appropriate Experimental Designsmentioning
confidence: 99%
“…When delivered by occupational therapy practitioners, home hazard removal programs have been shown to reduce falls by 39% among high-risk fallers in studies conducted in Europe (Nikolaus & Bach, 2003) and Australia (Clemson, Mackenzie, Ballinger, Close, & Cumming, 2008). In addition, home modification programs, which included hazard removal, to improve daily activity performance have demonstrated high acceptability and adherence among older adults in the United States (Gitlin, Corcoran, Winter, Boyce, & Hauck, 2001;Stark, Landsbaum, Palmer, Somerville, & Morris, 2009). However, a recent systematic review revealed that no randomized controlled trials (RCTs) have been conducted in the United States to examine the efficacy of home hazard removal to reduce falls (Stark, Keglovits, Arbesman, & Lieberman, 2017).…”
mentioning
confidence: 99%
“…Home modification interventions, such as architectural changes, assistive devices, and activity modification, typically target adults with functional limitations but also have the potential to reduce the need for physical care provided by caregivers (Agree & Freedman, 2000;Mortenson et al, 2012). Home modifications can increase functional performance for people with disabilities (Wahl, Fänge, Oswald, Gitlin, & Iwarsson, 2009), improve caregiver self-efficacy, and improve functioning for care recipients with dementia (Gitlin, Corcoran, Winter, Boyce, & Hauck, 2001;Graff et al, 2006). Furthermore, caregivers are receptive to environmental modification strategies; adherence rates for adaptation recommendations have been found to range from 65% (Dooley & Hinojosa, 2004) to 75% (Gitlin et al, 2001).…”
mentioning
confidence: 99%
“…Home modifications can increase functional performance for people with disabilities (Wahl, Fänge, Oswald, Gitlin, & Iwarsson, 2009), improve caregiver self-efficacy, and improve functioning for care recipients with dementia (Gitlin, Corcoran, Winter, Boyce, & Hauck, 2001;Graff et al, 2006). Furthermore, caregivers are receptive to environmental modification strategies; adherence rates for adaptation recommendations have been found to range from 65% (Dooley & Hinojosa, 2004) to 75% (Gitlin et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation